Classic Hodgkin lymphoma in Guatemalan children of age less than six years: analysis of immune regulatory pathways and the tumor microenvironment. Issue 7 (7th June 2021) - Silva, Oscar; Charu, Vivek; Ewalt, Mark D.; Metcalf, Ryan A.; Zhao, Shuchun; Castellanos, E. Mauricio; Orellana, Elizabeth; Natkunam, Yasodha; Luna-Fineman, Sandra
Abstract: Classic Hodgkin lymphoma (cHL) in young children (ages 0–6) is rare in high income countries (HICs) but is more prevalent in low- and middle-income countries (LMICs) like Guatemala. Given that the majority of cHL studies have evaluated adolescent/adults, and the immune system changes with age, we sought to characterize Epstein-Barr virus (EBV) expression, immune regulatory pathway markers and the tumor microenvironment in 42 children ages 0–6 with cHL from Guatemala. We found a very high frequency of EBV expression (97.5%). Hodgkin cells showed increased expression of PD1 ligands and CD137, indicative of shared immune regulatory mechanisms with adult cHL. Pediatric cHL also showed an increase in CD8+ tumor infiltrating lymphocytes and tumor associated macrophages within the tumor microenvironment. Despite 25 having high risk disease, only 4 patients died from progressive disease, relapse or infection.